Progression-free survival is a suboptimal predictor for overall survival among metastatic solid tumour clinical trials. (September 2020) - Pasalic, Dario; McGinnis, Gwendolyn J.; Fuller, C. David; Grossberg, Aaron J.; Verma, Vivek; Mainwaring, Walker; Miller, Austin B.; Lin, Timothy A.; Jethanandani, Amit; Espinoza, Andres F.; Diefenhardt, Markus; Das, Prajnan; et al.
Abstract: Background: The use of overall survival (OS) as the gold standard primary end-point (PEP) in metastatic oncologic randomised controlled trials (RCTs) has declined in favour of progression-free survival (PFS) without a complete understanding of the degree to which PFS reliably predicts for OS. Methods: Using ClinicalTrials.gov, we identified 1239 phase III oncologic RCTs, 260 of which were metastatic solid tumour trials with a superiority-design investigating a therapeutic intervention by using either a PFS or OS PEP. Each individual trial was reviewed to quantify RCT design factors and disease-related outcomes. Results: A total of 172, 133 patients were enrolled from the year 1999 to 2015 in RCTs that used PFS (56.2%, 146/260) or OS (43.8%, 114/260) as the PEP. PFS trials were more likely to restrict patient eligibility by using molecular criteria (15.1% versus 4.4%, p  = 0.005) use targeted therapy (80.1% versus 67.5%, p  = 0.048), accrue fewer patients (median 495 versus 619, p  = 0.03), and successfully meet the trial PEP (66.9% versus 33.3%, p  < 0.0001). On multiple binary logistic regression analysis, factors that predicted for PFS or OS PEP trial success included choice of PFS PEP ( p  < 0.0001), molecular profile restriction ( p  = 0.02) and single agent therapy ( p  = 0.02). Notably, there was only a 38% (31/82) conversion rate of positive PFS-to-OS benefit; lack of industry sponsorship predicted for PFS-to-OS signal conversion (80.0% without industry sponsorship versus 35.1% with industry sponsorship, p  = 0.045). Conclusions: A PFS PEP has suboptimal positive predictive value for OS among phase III metastatic solid tumour RCTs. Regulatory agency decisions should be judicious in using PFS results as the primary basis for approval. Highlights: Phase III metastatic trial utilization of progression-free (PFS) or overall survival (OS). PFS primary end-point (PEP) trials more likely to succeed (67%) versus OS PEP (33%). PEP success associated with molecular profile restriction and single agent therapy. PFS PEP trials had a subsequent OS benefit 38% of the time.